Gastrointestinal Cytoprotection by PPARγ Ligands - Naito, Yuji (Hindawi Publishing Corporation, 2010)
Peroxisome proliferator-activated receptor γ (PPARγ) is a nuclear receptor that is known to play a central role in lipid metabolism and insulin sensitivity as well as inflammation and cell proliferation. According to the results obtained from studies on several animal models of gastrointestinal inflammation, PPARγ has been implicated in the regulation of the immune response, particularly inflammation control, and has gained importance as a potential therapeutic target in the management of gastrointestinal inflammation. In the present paper, we present the current knowledge on the role of PPARγ ligands in the gastrointestinal tract.